Florida-Friendly Plants for Stormwater Pond Shorelines - Gail Hansen; Shangchun Hu (EDIS)
Selecting aquatic and shoreline plants for stormwater ponds is more challenging than selecting plants for a typical landscape. Site conditions can vary greatly and are more difficult to control. For example, water depth sometimes fluctuates widely, creating wet and dry conditions. Water quality varies with rainfall and fertilizer inputs. Steep slopes can make plant establishment and retention difficult. The concept of using the right plant in the right place is particularly important in the shoreline environment because the planting area includes a dry slope and a littoral shelf with shallow and deep-water areas. This 4-page fact sheet recommends plants that were selected based on these three questions: 1) What environmental conditions does the plant need to grow? 2) How do you want the plant to function? 3) What do you want the plant to look like? Written by Gail Hansen and Shangchun Hu, and published by the UF Department of Environmental Horticulture, May 2013.